2003
DOI: 10.4049/jimmunol.171.5.2504
|View full text |Cite
|
Sign up to set email alerts
|

The Block in Immunoglobulin Class Switch Recombination Caused by Activation-Induced Cytidine Deaminase Deficiency Occurs Prior to the Generation of DNA Double Strand Breaks in Switch μ Region

Abstract: Affinity maturation of the Ab repertoire in germinal centers leads to the selection of high affinity Abs with selected heavy chain constant regions. Ab maturation involves two modifications of the Ig genes, i.e., somatic hypermutation and class switch recombination. The mechanisms of these two processes are not fully understood. As shown by the somatic hypermutation and class switch recombination-deficient phenotype of activation-induced cytidine deaminase (AID)-deficient patients (hyperIgM type 2 syndrome) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 41 publications
4
57
1
Order By: Relevance
“…AID is expressed in activated B cells, especially in germinal centers of lymphoid follicles (6). Although AID is involved in the DNA cleavage step in CSR (7,8), its molecular mechanism is still controversial. The RNA-editing hypothesis postulates that AID converts unknown mRNA precursors to novel mRNAs encoding putative endonucleases to cleave the target DNA (6).…”
mentioning
confidence: 99%
“…AID is expressed in activated B cells, especially in germinal centers of lymphoid follicles (6). Although AID is involved in the DNA cleavage step in CSR (7,8), its molecular mechanism is still controversial. The RNA-editing hypothesis postulates that AID converts unknown mRNA precursors to novel mRNAs encoding putative endonucleases to cleave the target DNA (6).…”
mentioning
confidence: 99%
“…This transcription is sterile, in that the germ-line transcripts (GLT) are not translated into proteins (4, 24), and is presumably required to provide ssDNA either in the form of transcription bubbles (7) or R-loops with the nontranscribed strand being single stranded (13,14). The production of GLTs precedes the generation of AIDinduced mutations and of the DSB that are required for successful CSR (5,6,25).…”
mentioning
confidence: 99%
“…This transcription is sterile, in that the germ-line transcripts (GLT) are not translated into proteins (4, 24), and is presumably required to provide ssDNA either in the form of transcription bubbles (7) or R-loops with the nontranscribed strand being single stranded (13,14). The production of GLTs precedes the generation of AIDinduced mutations and of the DSB that are required for successful CSR (5,6,25).It has been suggested that increased accessibility contributes to the selective targeting to Ig genes and that this could be accomplished through modifications of chromatin that have been implicated in targeting transcription, replication, and other repair processes (26-28). It has been well established that modifications of histones H3 and H4 are essential for stepwise V(D)J recombination and additional steps in B cell differentiation (29,30).…”
mentioning
confidence: 99%
“…In addition, these studies established the mechanistic link between CSR and SHM by demonstrating that AID indeed initiates both events. DNA-dsb at IgH locus, as revealed by the formation of cH2AX and NBS1 foci or by LM-PCR, are no more detected in B cells from AID -/-mice and HIGM2 patients [66], thus indicating that AID acts upstream of the generation of DNA-dsb during CSR. Nevertheless, a dissociation of function between CSR and SHM was uncovered by the identification of HIGM patients presenting a CSR defect without alteration of SHM caused by particular mutations in the C terminus of AID.…”
Section: Higm: Csr and Shm Defectsmentioning
confidence: 93%